IMPLEMENTATION OF PROPORTIONAL AND PI ROASTING TEMPERATURE CONTROL IN DRUM-TYPE COFFEE ROASTER - Mohamad Nur Aulia Rachman; Budi Setiyono; Ajub Ajulian Zahra (Universitas Diponegoro, 2023)
Indonesia ranks as 4th highest coffee exporter by capacity and export value in the world, behind Brazil, Vietnam and Colombia. Statistics from The World Bank shows 2841 tons caffeinated roasted bean coffee from both varieties being exported from Indonesia throughout the world, while the National Statistics Board of Indonesia reported 380.173 tons of green bean coffee exported from Indonesia within 2019. Based on previous developments of coffee roasting technology, as this undergraduate thesis will explain about a coffee roaster prototype which is an improvement from previous researches, equipped with centralized temperature control and monitoring system from Artisan roasterscope that eases the operator or user’s workload to monitor the coffee beans’ roast level based on roast temperature and duration. In the experimentation of Ziegler-Nichols proportional control proves to give the best result for Robusta coffee with average rate of rise at 52.1° Celsius/min and average roast temperature of 140.8° Celsius which yields 100% roast uniformity at 95 Agtron roast scale. Following the addition of Astrom-Hagglund’s Proportional-Integral control, the result shows a formidable difference between each coffee bean varieties due to water content difference between both varieties. Keywords: coffee roasting, coffee roaster, proportional control, Artisan RoasterScope